Operational Strategy Analysis of Fashion Brands to Develop Digital Assets Under the Sustainability Goals - Yazhou Liu; Wenjie Wang; Junhua Liu (Systems)
This paper analyzes the strategic decisions of fashion brands regarding the development of digital assets based on blockchain technology, with a focus on achieving both sustainability and profitability goals. We first consider foundational factors such as the fashion value of products, their life cycle, and environmental taxes to construct a traditional fashion system involving the government, fashion brands, and consumers. Subsequently, we introduce a blockchain model that incorporates the added value of digital assets, the cost of technology, and the proportion of fashion consumers. Both models—traditional and digital—are solved mathematically, and numerical experiments are conducted to compare and analyze the impact of developing digital assets by fashion brands. The findings suggest that leveraging digital assets to enhance the fashion value of products can increase the profitability of fashion brands while also reducing environmental pollution caused by leftover inventory. Additionally, the development of digital assets may extend the life cycle of a product, although this does not always lead to improved environmental performance, highlighting a trade-off between the two objectives. Ultimately, the development of digital assets by fashion brands can result in a win-win for both profit and environmental performance, but this outcome is contingent on the cost of blockchain technology meeting specific conditions.